Sequencing of hepatitis C virus for detection of resistance to direct‐acting antiviral therapy: A systematic review. Issue 5 (22nd May 2017) - Bartlett, Sofia R.; Grebely, Jason; Eltahla, Auda A.; Reeves, Jacqueline D.; Howe, Anita Y.M.; Miller, Veronica; Ceccherini‐Silberstein, Francesca; Bull, Rowena A.; Douglas, Mark W.; Dore, Gregory J.; Harrington, Patrick; Lloyd, Andrew R.; et al.
Abstract : The significance of the clinical impact of direct‐acting antiviral (DAA) resistance‐associated substitutions (RASs) in hepatitis C virus (HCV) on treatment failure is unclear. No standardized methods or guidelines for detection of DAA RASs in HCV exist. To facilitate further evaluations of the impact of DAA RASs in HCV, we conducted a systematic review of RAS sequencing protocols, compiled a comprehensive public library of sequencing primers, and provided expert guidance on the most appropriate methods to screen and identify RASs. The development of standardized RAS sequencing protocols is complicated due to a high genetic variability and the need for genotype‐ and subtype‐specific protocols for multiple regions. We have identified several limitations of the available methods and have highlighted areas requiring further research and development. The development, validation, and sharing of standardized methods for all genotypes and subtypes should be a priority. ( Hepatology Communications 2017;1:379–390)